Adrenal Incidentalomas with Supraphysiologic Response to ACTH Stimulus: A Case Report. (14th October 2012) - Antonopoulou, Marianna; Perelstein, Asya
Abstract : We present the diagnostic approach of a patient with adrenal incidentalomas. A 72-year-old African American male had a CT scan of the abdomen showing right and left adrenal masses measuring 5 × 3.5 cm and 3.7 × 2.9 cm, respectively. The patient had negative hormonal workup. The radiologist insisted that the CT findings are consistent with adrenal hyperplasia, and therefore he underwent ACTH stimulation to rule out late-onset congenital adrenal hyperplasia (CAH). The stimulation test revealed that 17-hydroxyprogesterone and 11-deoxycortisol increased to levels high enough to confirm CAH, but cortisol had exaggerated response as well, thus making the diagnosis of CAH unlikely where metabolism is shifted to precursors. Subsequently, the patient underwent screening for Cushing's syndrome (CS) with a dexamethasone suppression test. Patient failed the suppresion test, raising the issue for subclinical CS (SCS), likely due to ACTH-independent macronodular adrenal hyperplasia. Our patient had been diagnosed with MGUS and so far there are only 3 case reports of extramedullary plasmacytoma arising from the adrenals. One was bilateral and one had functional abnormalities. Our differential diagnosis includes subclinical CS with aberrant receptors versus a functioning extramedullary plasmacytoma.